2013
DOI: 10.1371/journal.pone.0067504
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin Alleviates the Inhibitory Effects of High Glucose on the Osteoblastic Differentiation of Periodontal Ligament Stem Cells

Abstract: Hesperetin (3′,5,7-trihydroxy-4-methoxyflavanone) is a metabolite of hesperidin (hesperetin-7-O-rutinoside), which belongs to the flavanone subgroup and is found mainly in citrus fruits. Hesperetin has been reported to be an effective osteoinductive compound in various in vivo and in vitro models. However, how hesperetin effects osteogenic differentiation is not fully understood. In this study, we investigated the capacity of hesperetin to stimulate the osteogenic differentiation of periodontal ligament stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 43 publications
6
56
0
1
Order By: Relevance
“…NO is known to induce osteogenesis of ESCs through activation of canonical Wnt signaling [21]. More recently, our group has reported that Wnt signaling is associated with the osteogenic differentiation of stem cells under various experimental conditions [41][42][43]. Based on previous studies and our present data, we suggest that NO can activate wide spectrum of signaling pathways involved in the osteogenic differentiation of stem cells.…”
Section: Discussionsupporting
confidence: 74%
“…NO is known to induce osteogenesis of ESCs through activation of canonical Wnt signaling [21]. More recently, our group has reported that Wnt signaling is associated with the osteogenic differentiation of stem cells under various experimental conditions [41][42][43]. Based on previous studies and our present data, we suggest that NO can activate wide spectrum of signaling pathways involved in the osteogenic differentiation of stem cells.…”
Section: Discussionsupporting
confidence: 74%
“…Two studies (Jittapiromsak et al ., ; Kim et al ., ) did not provide any information about the cell proliferation assay, and six studies analysed cell proliferation (Gao et al ., ; Nowwarote et al ., ; Pei et al ., ; Boonanantanasarn et al ., ; Chantarawaratit et al ., ; Kim et al ., ). Furthermore, six studies used the MTT assay to evaluate cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological functions of stems cells are altered by different microenvironments, such as high glucose, inflammation, and hypoxia [9][10][11]. We found that high glucose microenvironments at 16.5 mM affect proliferation, differentiation, and mineralization of rat mandibular osteoblasts compared with physiological concentration of glucose (5.5 mM) [12], although the process of stem cell-mediated bone regeneration requires the simultaneous interplay of a variety of factors.…”
Section: Introductionmentioning
confidence: 82%